Evaluation of Power Generated by using Savonius Horizontal Axis Water Turbine - Shaiful Hizam, Nayli Fariesya; Mohd, Sofian; Sofian Mohd (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study focuses on the fabrication and analytical calculations of a Savonius Horizontal Axis Water Turbine (SHAWT) for power generation. The fabrication involves the construction of a turbine with twisted blades at a 90˚ angle, incorporating a shaft, ball bearing, and supporting frame, along with the use of a DC motor. Analytical calculations were conducted to estimate the maximum power output of the turbine. The calculations indicated a power output range of 3.35 to 4.64 MW at water velocities ranging from 28.0 to 31.3 m/s based on the height of waterfall in Gunung Pulai ranged in 40 to 50 meter. The calculations considered factors such as water velocity, blade design, and efficiency based on Betz Law, providing valuable insights into the turbine's power generation potential. While the analytical calculations provide estimations based on theoretical assumptions, experimental validation is necessary to confirm the accuracy and reliability of the results. Future work should include experimental testing to compare the calculated power output with actual measurements, enabling a comprehensive evaluation of the turbine's performance. Overall, this study contributes to the understanding of the fabrication and analytical calculations involved in the design and estimation of the maximum power output of a SHAWT. Further experimental validation will enhance the reliability and practical application of the results.